Clinical results of vulvar cancer treatment in early stages based on sentinel lymph node biopsy and classic surgical treatment in the Institute of Oncology of Vilnius University between 2011 and 2013 - Žilinskas, Kastytis; Maculevič, Kristina; Volochovič, Jelena; Zakarevičienė, Jolita (Acta medica Lituanica, 2014)
Background. Radical vulvectomy accompanied by bilateral inguinal lymph nodes dissection (ILND) has been performed to treat cancer for a long time but, due to various short and long term postoperative complications, alternatives have been found. The objective was to compare the clinical results of vulvar cancer treatment in early stages based on sentinel lymph node(s) biopsy (SLNB) and classic surgical treatment and to evaluate the radiological safety of SLNB. Materials and methods. Retrospective study involved 26 patients with clinical stage I–II of vulvar carcinoma treated in the Institute of Oncology, Vilnius University, between 2011 and 2013. The women were divided into two groups: 14 patients underwent a reduced surgical treatment based on the SLNB method, and 12 patients underwent a classic surgical treatment. Results. After SLNB and intraoperative histological examination, 9 patients in the first group underwent radical tumour excision, while the others underwent ipsilateral or bilateral ILND. Final histological examination detected metastases in lymph nodes in 4 patients from the first group and 3 patients from the second group. The average surgery duration on the patients undergoing only SLNB and radical tumour excision was 77.2 minutes, and the classical surgery took 177.7 minutes. Average exposure levels measured in the first group reached up to 1 µSv/hour. Conclusions. Surgery treatment based on SLNB for patients with early stages of vulvar carcinoma can reduce the extent of surgical interventions. Exposure limits to the patients and staff were safe.
Keywords: vulvar cancer treatment; sentinel lymph node; technetium (99mTc) albumin nanocolloid; vital blue dye